Test of Faith when Experienced Temptation Based on James 1:2-3 - Janes Sinaga; Kingston Pandiangan; Beni Chandra Purba; Juita Lusiana Sinambela (PT FORMOSA CENDEKIA GLOBAL, 2023)
Suffering and trials seem unavoidable in every aspect of life. Problems happen to everyone, even experienced by believers. Sometimes when trials occur, some think temptations come from God so they tend to make trouble with God. The purpose of this research is for every believer to understand that trials are not God's plan, but God allows trials to occur as a means of testing the faith of every one of His people. This study uses descriptive qualitative research methods by analyzing and concluding data obtained from library sources such as the Bible, journals and books. Trials do not come from God, but when His people experience trials, God will be ready to provide help to give strength